Helicobacter pylori: qué debemos saber en el año 2018. Revisión de la evidencia y nuevas recomendaciones de tratamiento - da Costa G., Daniel; Defilippi G., Claudia (Revista Hospital Clínico Universidad de Chile, 2019)
Helicobacter pylori (HP) is the most widely chronic human infection around the world, andthe main risk factor for the development of gastric cancer. Our country has high rates ofthis neoplasia and a high prevalence of HP infection. Even both have fallen in the last year,is a major concern to diagnose the population infected with HP in early stages, before thedevelopment of premalignant lesions and properly eradicate this infection. In this review, wediscussed the different methods for the diagnosis of HP and factors that change positivityas the use of proton pump inhibitors. Also, we discussed the factors to be considered in thechoice of the treatment, like local resistance to antibiotics, specially clarithromycin. In the lastyears has been documented in Chile a significant increase in resistance to clarithromycin, from20 to 46%, which predicts inadequate effectiveness for the classic triple therapy. As the resultof the previous analysis we discussed new possible therapies, including bismuth quadrupletherapy and concomitant therapy.